Marketing Strategies of Microfinance Institutions within Kwara Metropolis of Nigeria: Case of Kwara Institutions - Jimba, Kareem; Babalola, Gboyega E. (African Journal of Stability and Development (AJSD), 2019)
This study focuses on identifying whether microfinance institutions (MFIs) within Kwara metropolis use marketing approaches and strategies in savings mobilisation and credit delivery. The basic source of data for this study is primary data. The data were collected from the credit officers and in some cases management team of the microfinance institutions. Descriptive statistics were employed for the analysis of the data. Concerning their marketing objectives, mission statements, strategy and approaches, the study found that the selected microfinance institutions are not market[1]oriented in the delivery of their services. Among the recommendations made are that MFIs should create marketing departments, fashion out customer service packages, and strengthen their marketing planning capabilities especially as these border on the creation of environmental awareness.